2003
DOI: 10.1021/om030018t
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl Polymerization of Norbornene with Neutral Salicylaldiminato Nickel(II) Complexes

Abstract: A series of neutral salicylaldiminato Ni(II) complexes have been synthesized and characterized, and complexes a and e have been confirmed by X-ray single-crystal analyses. These compounds show highly catalytic activities for the vinyl polymerization of norbornene with MAO cocatalyst, which could be up to 2.86 × 108 g PNB/(mol Ni·h), and also lead to various activities, molecular weights, and distributions of polynorbornenes under different reaction conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
68
0
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(72 citation statements)
references
References 29 publications
3
68
0
1
Order By: Relevance
“…In comparison, unsubstituted PNBs can be dissolved only in chlorobenzene or decaline (M < 8 Â 10 4 in chloroform). [16,17] The GPC results from THF solutions are listed in Table 1, and show that the reasonably high molecular weights, relatively narrow polydispersity index values, and good yields are obtained for PNB-dialkyl esters.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison, unsubstituted PNBs can be dissolved only in chlorobenzene or decaline (M < 8 Â 10 4 in chloroform). [16,17] The GPC results from THF solutions are listed in Table 1, and show that the reasonably high molecular weights, relatively narrow polydispersity index values, and good yields are obtained for PNB-dialkyl esters.…”
Section: Resultsmentioning
confidence: 99%
“…When activated with MAO compounds Ni-69 to Ni-74 were very efficient catalysts with activities of more than 10 8 g polymer /mol Ni h. There was practically no influence of the ligand structures on the polymer yields [156]. The system Ni-69/MAO was used for further investigations concerning the polymerization parameters.…”
Section: No-(ns-)chelate Ligandsmentioning
confidence: 99%
“…Ni-69/MAO showed good activities over a wide temperature range from 0 • C to 100 • C. The temperature influenced the activities only slightly, whereas the NB/Ni ratio greatly affected the activity. It was shown that at least a NB/Ni ratio of 10 000 was required to give polynorbornene in good yields and for a ratio of 25 000 an excellent activity of 2.6 × 10 8 g PNB /mol Ni h was obtained [156].…”
Section: No-(ns-)chelate Ligandsmentioning
confidence: 99%
“…12.024. weakly coordinating counter ions like BF À 4 or PF À 6 (Ni, Pd). We have been engaging in the research of Schiff base-containing nickel complex-catalyzed ethylene polymerization, and we have extensively investigated the vinyl polymerization of norbornene catalyzed by nickel complexes liganded by 8-(diphenylphosphino)quinoline [23] and salicylideneimide [24]. In this paper, we describe the design and synthesis of a series of new bis(1-aryliminomethylenylnaphthalen-2-oxy)nickel complexes and the examination of their catalytic activities for norbornene polymerization.…”
Section: Introductionmentioning
confidence: 99%